Mars Land Use Policy Implementation: Approaches and Best Methods. (August 2021) - Dapremont, Angela M.
Abstract: Sending humans to Mars has been a component of the official US space policy of multiple presidential administrations. Additional stakeholders with interests in visiting Earth's terrestrial neighbor in the coming decades include private companies and the space agencies of other spacefaring nations. Numerous motivations exist for humans to explore and settle on the Martian surface, including environmental suitability and species survival, the search for life, scientific and technological development, economic profitability, and fundamental human nature. However, if human settlement and sustainability on Mars is expected to become a reality, existing legal regime deficiencies must be addressed, six of which I have identified: (1) national jurisdiction and responsibilities, (2) resource utilization, (3) conflict resolution and central authority, (4) environmental protection, (5) future settler legal status, and (6) social justice. This article examines the feasibility of various land use policies applied to the Mars case. I conduct a policy option evaluation of the following proposed land use approaches using assessment criteria based on the identified legal deficiencies: (1) bounded first possession by landfall [Collins, 2008], (2) bounded possession with planetary parks [Bruhns and Haqq-Misra, 2016], (3) liberating Mars [Haqq-Misra, 2015], (4) a Mars tax [Collins, 2008], and (5) planetary parks [Cockell and Horneck, 2004]. Based on this analysis, I recommend approach (2), which allows for bounded possession and creates planetary parks. This approach sufficiently addresses all assessment criteria by permitting occupation and resource rights to limited plots of land on the Martian surface, advocating for a Mars Secretariat as a conflict mediation method, implementation of a planetary park system to protect valuable lands, and designating the application of laws within and outside of land claim areas. Implications of the findings presented here are valuable not only for the future exploration and settlement of Mars but other solar system bodies where human activity may be an eventual reality.